Decolonizing the diet : nutrition, immunity, and the warning from early America - Mailer, Gideon; Hale, Nicola E., 1985- (Anthem Press, 2018)
Decolonizing the Diet challenges the common claim that native American communities were decimated after 1492 because they lived in virgin soils that were biologically distinct from those in the Old World. Comparing the European transition from Paleolithic hunting and gathering with native American subsistence strategies before and after 1492, this book offers a new way of understanding the link between biology, ecology and history. After examining the history and bio-archaeology of ancient Europe, the ancient Near East, ancient native America and Europe during the medieval Black Death, this study sets out to understand the subsequent collision between Indigenous peoples and Europeans in North America from 1492 to the present day. Synthesizing the latest work in the science of nutrition, immunity and evolutionary genetics with cutting edge scholarship on the history of Indigenous North America, this book highlights a fundamental model of human demographic destruction human populations have been able to recover from mass epidemics within a century, whatever their genetic heritage. They fail to recover from epidemics when their ability to hunt, gather and farm nutritionally dense plants and animals is diminished by war, colonization and cultural destruction. The history of native America before and after 1492 clearly shows that biological immunity is contingent on historical context, not least in relation to the protection or destruction of long-evolved nutritional building blocks that underlie human immunity. --